Il Concetto della Giustizia Secondo l’Alligatore di Massimo Carlotto - Mohamed, Lamiaa Aly Mosselhy (European Journal of Sustainable Development, 2019)
Through the hard-boiled work of Massimo Carlotto, the research verifies the concept of justice according to his protagonist, the Alligator, an ex-musician, ex-convict and a new private detective. This character discovers a conspiracy well managed years ago in order to save the real guilty person, Mugwump’s son, from a murder and send to prison another one instead of him. This new fact (motivates/ urges/ forces) to him decide to declare the (victim’s/ imprisoned man’s) innocence and restore his dignity back to him. The power of a corrupted lobby and his past as an ex-prisoner prevent him to present evidence, not always collected by legal means, to justice, so he decides to achieve justice by his own and innovative tools in addition to using his own distinguished skills. In the introduction, I elaborated the reasons of choosing a modern writer like Carlotto. The first chapter is dedicated to the characteristics of this gender of mystery work and I provided examples through the writer’s work. In the second chapter, I underlined the skills and the modality which reflect the concept of justice adopted by the writer. Finally in the third chapter, I discussed about Carlotto’s style. Keywords.Carlotto; Alligatore; giustizia; stampa; hard boiled; delitti.